PELAKSANAAN PEMBELAJARAN PENDIDIKAN SENI BUDAYA (MUSIK) DI KELAS X SMAN I NAN SABARIS KABUPATEN PADANG PARIAMAN - Renovica Madilla; Yos Sudarman; Harisnal Hadi (SENDRATASIK UNP, 2018)
Abstract This article aims to look at and describe the implementation of learning art and cultural education (music) at SMAN 1 Nan Sabaris Padang Pariaman. Type of this research is descriptive research. This research instrument is its own researchers and researchers helped by supporting instruments such as observation records and documents. This type of research is the primary data and secondary data and the data of the test i.e. non through interviews and observations in a sample of research. The format of the assessment using the observation formats check list or a percentage scale then described with descriptive analysis. The results showed that interpersonal communication through which implement all methods of learning, teacher at SMAN I Nan Sabaris succeed in the learning process. Communication strategy group that is applied to include activity planning, implementation and evaluation. Teaching and learning through interpersonal communication, either teachers or pupils can understand each other and understand each character so that the educational process can take place properly and effectively. Keywords: implementation, learning, art and culture (music)